2016
DOI: 10.1371/journal.pone.0161796
|View full text |Cite
|
Sign up to set email alerts
|

15d-PGJ2-Loaded Solid Lipid Nanoparticles: Physicochemical Characterization and Evaluation of Pharmacological Effects on Inflammation

Abstract: 15-deoxy-Δ12,14-prostaglandin J2 (15d-PGJ2), a peroxisome proliferator-activated receptor-γ (PPAR-γ) agonist, has physiological properties including pronounced anti-inflammatory activity, though it binds strongly to serum albumin. The use of solid lipid nanoparticles (SLN) can improve therapeutic properties increasing drug efficiency and availability. 15d-PGJ2-SLN was therefore developed and investigated in terms of its immunomodulatory potential. 15d-PGJ2-SLN and unloaded SLN were physicochemically characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 35 publications
1
8
0
1
Order By: Relevance
“…Through mathematical fitting, it was possible to compare the two release curves, and the constant values (k) demonstrated that BENZ is released faster from NPMAs than NPs due to the presence of chitosan coating, which probably translocates BENZ molecules from the surface. The values of r indicated the main mechanism involved in the release of the drug was Fickian diffusion, as also found previously for other polymeric nanoparticles containing articaine [24,25] and solid lipid nanoparticles containing prostaglandin J 2 [27] .…”
Section: Plos Onesupporting
confidence: 84%
See 3 more Smart Citations
“…Through mathematical fitting, it was possible to compare the two release curves, and the constant values (k) demonstrated that BENZ is released faster from NPMAs than NPs due to the presence of chitosan coating, which probably translocates BENZ molecules from the surface. The values of r indicated the main mechanism involved in the release of the drug was Fickian diffusion, as also found previously for other polymeric nanoparticles containing articaine [24,25] and solid lipid nanoparticles containing prostaglandin J 2 [27] .…”
Section: Plos Onesupporting
confidence: 84%
“…Mathematical modeling was employed to elucidate the drug release from the nanoparticle systems. The Baker-Lonsdale model has been used previously by our group to evaluate the results of release curves involving nanoparticles [ 24 , 25 , 27 ]. Linear regression showed correlation coefficient ( r ) values of 0.978 and 0.988, and release constant ( k ) values of 4.24822 x 10 −5 (± 2.83661 x 10 −6 ) min -1 and 6.65378x 10 −5 (± 4.27674 x 10 −6 ) min -1 , for NPs and NPMAs, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nanocapsules consist of polymeric involucres around a nucleus generally oily used to prolong pharmacological activity and decrease toxicity of molecules 20 . 15d-PGJ 2 was shown to be released slowly from nanocapsules, which avoided inactivation or reduction of its biological activity 21 , 22 by reactions that could include Michael’s addition 23 . Another possibility is that cells could uptake nanoparticles loaded with 15d-PGJ 2 resulting in enhanced 15d-PGJ 2 levels inside the cells as well as increased pharmacological response.…”
Section: Introductionmentioning
confidence: 99%